2017
DOI: 10.1002/hed.24992
|View full text |Cite
|
Sign up to set email alerts
|

Potential for health care cost savings with preoperative gastrostomy tube placement in the head and neck cancer population

Abstract: Background: The purpose of this study was to examine the cost differences between preoperative and postoperative placement of gastrostomy tubes (G-tubes) in patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
7
2
Order By: Relevance
“…In patients with laryngeal SCC, we found that higher quality care was not associated with late dysphagia but was associated with improved survival when dysphagia was present. [13][14][15] The majority of patients with OPSCC treated with radiation have a gastrostomy placed before or during treatment, despite a growing body of evidence that suggests that prophylactic gastrostomy placement is associated with worse long-term swallowing outcomes. These data suggest that dysphagia is common in laryngeal SCC, but its sequela is responsive to differences in quality of care, with progression to gastrostomy dependence less likely with higher quality care but survival unaffected by quality once gastrostomy dependence was present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with laryngeal SCC, we found that higher quality care was not associated with late dysphagia but was associated with improved survival when dysphagia was present. [13][14][15] The majority of patients with OPSCC treated with radiation have a gastrostomy placed before or during treatment, despite a growing body of evidence that suggests that prophylactic gastrostomy placement is associated with worse long-term swallowing outcomes. These data suggest that dysphagia is common in laryngeal SCC, but its sequela is responsive to differences in quality of care, with progression to gastrostomy dependence less likely with higher quality care but survival unaffected by quality once gastrostomy dependence was present.…”
Section: Discussionmentioning
confidence: 99%
“…12 The addition of chemotherapy to radiation is associated with an increase in dysphagia as well as an increased use of prophylactic and therapeutic gastrostomy placement in an effort to reduce weight loss and treatment-related complications. [13][14][15] The majority of patients with OPSCC treated with radiation have a gastrostomy placed before or during treatment, despite a growing body of evidence that suggests that prophylactic gastrostomy placement is associated with worse long-term swallowing outcomes. [16][17][18][19][20][21][22][23][24] In addition to chemotherapy, there is a known relationship between radiation dose and the extent of short-term and longterm soft tissue toxicity, with doses >60 Gy associated with an increased risk of late dysphagia and gastrostomy use.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of swallowing to overall quality of life and the negative impact on quality of life of gastrostomy tube feedings, this information may play a role in patients’ decisions to proceed with surgery vs other forms of treatment 11,29 . Appropriately stratifying elderly patients at high risk for poor postoperative swallowing may allow for health care cost savings and decreased length of stay through preoperative gastrostomy tube placement 30 . In terms of longitudinal swallowing function, these data can be used to counsel elderly patients that most patients who achieve good swallowing function do so within 1 month of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…11,29 Appropriately stratifying elderly patients at high risk for poor postoperative swallowing may allow for health care cost savings and decreased length of stay through preoperative gastrostomy tube placement. 30 In terms of longitudinal swallowing function, these data can be used to counsel elderly patients that most patients who achieve good swallowing function do so within 1 month of surgery.…”
Section: Implications For Patient Carementioning
confidence: 99%
“…[21][22][23] A medical history including hypertension, a normal/underweight BMI, and depressive symptoms have been associated with increased risk for ED presentation. 17 With regard to peri-operative factors, prophylactic percutaneous gastronomy tube (PEG) placement has been associated with lower rates of hospital readmissions, 24,25 and airway management with tracheostomy has been associated with prolonged LOS. 26 Finally, in terms of post-operative factors, medical/surgical complications (e.g., pneumonia, wound infection, hemorrhage) have been associated with prolonged LOS and readmissions.…”
Section: Introductionmentioning
confidence: 99%